Therapeutic expression of human clotting factors IX and X following adeno-associated viral vector-mediated intrauterine gene transfer in early-gestation fetal macaques - Chan, Jerry K. Y.; Gil-Fariña, Irene; Schmidt, Manfred (The FASEB journal, 2019)
Adeno-associated viral vectors (AAVs) achieve stable therapeutic expression without long-term toxicity in adults with hemophilia. To avert irreversible complications in congenital disorders producing early pathogenesis, safety and efficacy of AAV-intrauterine gene transfer (IUGT) requires assessment. We therefore performed IUGT of AAV5 or -8 with liver-specific promoter-1 encoding either human coagulation factors IX (hFIX) or X (hFX) into Macaca fascicularis fetuses at ∼0.4 gestation. The initial cohort received 1 × 1012 vector genomes (vgs) of AAV5-hFIX (n = 5; 0.45 × 1013 vg/kg birth weight), resulting in ∼3.0% hFIX at birth and 0.6-6.8% over 19-51 mo. The next cohort received 0.2-1 × 1013 vg boluses. AAV5-hFX animals (n = 3; 3.57 × 1013 vg/kg) expressed <1% at birth and 9.4-27.9% up to 42 mo. AAV8-hFIX recipients (n = 3; 2.56 × 1013 vg/kg) established 4.2-41.3% expression perinatally and 9.8-25.3% over 46 mo. Expression with AAV8-hFX (n = 6, 3.12 × 1013 vg/kg) increased from <1% perinatally to 9.8-13.4% >35 mo. Low expressers (<1%, n = 3) were postnatally challenged with 2 × 1011 vg/kg AAV5 resulting in 2.4-13.2% expression and demonstrating acquired tolerance. Linear amplification-mediated-PCR analysis demonstrated random integration of 57-88% of AAV sequences retrieved from hepatocytes with no events occurring in or near oncogenesis-associated genes. Thus, early-IUGT in macaques produces sustained curative expression related significantly to integrated AAV in the absence of clinical toxicity, supporting its therapeutic potential for early-onset monogenic disorders.—Chan, J. K. Y., Gil-Farina I., Johana, N., Rosales, C., Tan, Y. W., Ceiler, J., Mcintosh, J., Ogden, B., Waddington, S. N., Schmidt, M., Biswas, A., Choolani, M., Nathwani, A. C., Mattar, C. N. Z. Therapeutic expression of human clotting factors IX and X following adeno-associated viral vector-mediated intrauterine gene transfer in early-gestation fetal macaques.
Gesehen am 01.04.2019